Brazilian Fascism: The Extreme Right and the Forever-Present Past (Revista Tempo e Argumento, 2024)
Book review: GONÇALVES, Leandro Pereira; CALDEIRA NETO, Odilon. Fascism in Brazil: From Integralism to Bolsonarism. London, and New York: Routledge, 2022.